Adhesion of NCF to oxidized Si wafers after oxygen plasma treatment. (November 2017) - Jang, Min-Seok; Ma, Sung Woo; Song, Jongsoo; Sung, Myungmo; Kim, Young-Ho
Abstract: The effect of oxygen plasma treatment on the adhesion between nonconductive film (NCF) and oxidized Si was investigated. Oxidized Si wafers were treated with oxygen plasma for 5 min and then rinsed in de-ionized water (DIW). The water contact angle was measured by means of the sessile drop technique and the surface roughness was measured by means of atomic force microscopy. The adhesion of the NCF to the oxidized Si wafer was evaluated by means of a single-lap shear test after bonding at 150°C for 5 s. Oxygen plasma treatment decreased the water contact angle. The roughness of the oxidized Si wafer decreased when oxygen plasma treatment was applied alone, but was increased when both oxygen plasma treatment and DIW rinse were applied. Similarly, the shear strength decreased when oxygen plasma treatment was applied alone, but the adhesion of NCF increased when both oxygen plasma treatment and DIW rinse were applied. The increased surface roughness of the oxidized Si wafer played an important role in increasing the adhesion between the NCF and the oxidized Si wafer. The shear strength further increased after post-heat treatment at 170°C for 1 hr or at 280°C for 15 s. Low shear strength observed before post-heat treatment was ascribed to incomplete NCF curing. Differences observed in the adhesion strength between two types of NCF were attributed to differences in their curing degrees and their degrees of surface coverage of the oxidized Si substrates. Highlights: We investigated the effects of O2 plasma on the adhesion of NCFs to SiO2 substrates. Effects of post-heat treatment on the adhesion were investigated. Although O2 plasma treatment improved wettability, it did not increase the adhesion. The DI water rinse after O2 plasma treatment increased the adhesion. Post-heat treatment increased the adhesion by increasing the curing degree of NCFs.